The American legal profession in crisis resistance and responses to change - Moliterno, James E., 1953- (New York : Oxford University Press, 2013)
Central to the identity of the American legal profession are its systems of self-regulation. Throughout history, the legal profession has tried to hold tight to its traditional values and structure during times of self-identified crisis. This book analyzes the efforts of the legal profession to protect and maintain the status quo even as the world around it changed. The book argues that with striking consistency, the profession has resisted the societal change happening around it, and sought to ban or discourage new models of legal representation created by such change.
Description based on online resource; title from home page (viewed on Mar. 12, 2013).
Includes bibliographical references and index.
Keywords: Practice of law -- United States; Practice of law -- United States -- History -- 20th century; Law -- Social aspects -- United States; Social change -- United States